PROTECTIVE EFFECTS OF COMBINED VITAMIN E AND ZINC SULFATE ON OVARIAN AND UTERUS WEIGHT OF ALBINO RATS (Rattus norvegicus) EXPOSED TO LEAD ACETATE - Fitriani Sultan; Tri Wahyu Suprayogi; Rimayanti; Ragil Angga Prastiya; Bodhi Agustono; Amung Logam Saputro (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2026)
Lead exposure exerts toxic effects on the female reproductive system, particularly on the ovaries and uterus, resulting in hypofunction and organ atrophy. Oxidative stress induced by lead accumulation may be attenuated by antioxidants such as vitamin E and zinc sulfate. This study aimed to evaluate the protective effects of vitamin E, zinc sulfate, and their combination on ovarian and uterus weights in albino rats (Rattus norvegicus) exposed to lead acetate. Twenty-five female rats were randomly divided into five groups (K, T0, T1, T2, and T3) and treated orally for 21 days. On day 22, the rats were euthanized, and the ovaries and uterus were collected and weighed. The average ovarian weights for K, T0, T1, T2, and T3 were 25.80 ± 2.49; 18.62 ± 4.36; 28.40 ± 5.67; 33.78 ± 6.09; and 36.84 ± 5.15 mg, respectively. The average uterus weights for K, T0, T1, T2, and T3 were 292.48 ± 36.81; 249.96 ± 25.97; 315.86 ± 26.56; 325.54 ± 31.53; and 375.00 ± 36.55 mg, respectively. In conclusion, vitamin E and zinc sulfate demonstrated protective effects against lead-induced reproductive toxicity, with the combined treatment showing the greatest improvement in ovarian and uterus weights.